ANALYSIS OF FREQUENCY AND STRUCTURE OF OUT-PATIENT SURGERY IN PROVIDING DENTAL CARE - Гоголь, А.М.; Pankevych A, I.; Колісник, І.А. (World of Medicine and Biology, 2015)
The article presents the results of statistical analysis of archival material on surgical operations in KU "Poltava regional center for dentistry - dental clinical policlinic" for the period from 2005 to 2014. 1920 surgical operations were conducted during this period. Operations conducted the staff of department of propaedeutics of surgical dentistry (Higher State Education Institution “Ukranian Medical Stomatological Academy” Poltava).The orthodontic pathology amounted 44%, inflammatory processes in oral cavity and head – 36%, periodontal diseases – 7%, tumours and tumours-like formation of soft tissues – 6%, tumours and tumours-like formation of osseous tissues – 4%, background for prosthesis – 2% in structure of all surgical operations.To orthodontic indications for surgery were included next pathological conditions: dystopia and retention of permanent teeth, supernumerary teeth, abnormalities of attachment of lip and tongue fraenulum’s, and dental germectomy. Surgical extraction is main procedure for removal of teeth. The fraenulum’s of mucous membrane in oral cavity were eliminated by single-stage fraenulectomy.Surgery for inflammatory diseases in oral cavity and head was composed from incision and drainage of abscess in soft tissues, as complications of chronic periapical inflammations or pericoronitis, and operations allowing you to save of teeth. The latter includes resection of root apex, dental hemi section, crown-radicular separation, root amputation, tooth replantation, and removal of granulation tissues. These are surgical treatment of chronic periapical infection or inflammation in root bifurcation of lower molars.The incision and drainage of submucous abscess by periodontal disease most frequently performed in the case of emergency. The flap surgery with using osteoplastic materials for regenerative process in periodontium more often conducted on lower jaw. Odontogenic inflammatory cysts were amounted 92, 7% in cases of surgery by tumours and tumour-like formations of jaws. Cystectomy with followed filling osteoplastic material in bone defect was usual procedure in most cases. The method of cystotomy with iodoform packing was used if cysts have bigger size. The incision and drainage of cyst was conducted when suppuration join to process. The retention cyst of small salivary gland amounted 23%, epulis – 19, 65%, fibromas – 17%, papilomas – 9, 4% in structure of tumours and tumours-like formations of soft tissues. Traditional method of benign tumour excision and diathermocoagulation were used for patient treatment. Diagnosis was confirmed by histological examination. Received results of statistical analysis have practical significance. In particular, they are objective accord of prevalence of diseases which requires of oral and maxillofacial surgery, and may indicate about effectiveness their prophylaxis and treatment. Findings may be used for improving surgical care in public hospitals and planning scientific research in dentistry.
Keywords: maxillo-facial area; out-patient surgery; statistical analysis